Framework for Assessing the Feasibility of Carbon Dioxide Removal Options Within the National Context of Germany - Förster, Johannes; Beck, Silke; Borchers, Malgorzata; Gawel, Erik; Korte, Klaas; Markus, Till; Mengis, Nadine; Oschlies, Andreas; Schaller, Romina; Stevenson, Angela; Thoni, Terese; Thrän, Daniela (Frontiers in Climate, 2022)
Removal of carbon dioxide from the atmosphere will be required over the next decades to achieve the Paris Agreement goal of limiting global warming to well below 2°C aiming at not exceeding 1.5ºC (IPCC 2018). Technological and ecosystem-based options are considered for generating negative emissions through carbon dioxide removal (CDR) and several nations have already included these in their Long-Term Low Greenhouse Gas Emission Development Strategies. However, strategies for development, implementation, and upscaling of CDR options often remain vague. Considering the scale at which CDR deployment is envisioned in emission pathways for limiting global warming to 1.5ºC, significant environmental, social, and institutional implications are to be expected and need to be included in national feasibility assessments of CDR options. Following a multi-disciplinary and holistic approach, we created a framework that considers the environmental, technological, economic, social, institutional, and systemic implications of upscaling CDR options. We propose the framework as a tool to help guide decision-relevant feasibility assessments of CDR options, as well as identify challenges and opportunities within the national context. As such, the framework can serve as a means to inform and support decision makers and stakeholders in the iterative science-policy process of determining the role of CDR options in national strategies of achieving net-zero carbon emissions.